2018
DOI: 10.1089/ham.2018.0044
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypoxia on Cardiovascular Disease: Friend or Foe?

Abstract: Savla, Jainy J., Benjamin D. Levine, and Hesham A. Sadek. The effect of hypoxia on cardiovascular disease: Friend or foe? High Alt Med Biol. 19:124-130, 2018.-Over 140 million people reside at altitudes exceeding 2500 m across the world, resulting in exposure to atmospheric (hypobaric) hypoxia. Whether this chronic exposure is beneficial or detrimental to the cardiovascular system, however, is uncertain. On one hand, multiple studies have suggested a protective effect of living at moderate and high altitudes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 88 publications
(92 reference statements)
0
35
0
1
Order By: Relevance
“…In addition, hypoxia stimulates hypoxia inducible factor 1, the main regulator in the expression of the leptin gene-a hormone secreted by adipose tissue that has a negative feedback on appetite-and inversely associated with obesity (Sierra-Johnson et al 2008). A cross-sectional study conducted at different altitudes in the Everest region of Nepal also found that obesity decreased with increasing altitude (Sherpa et al 2010). Our findings present a striking example of the variation in obesity prevalence found among populations of similar indigenous backgrounds under different environmental circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoxia stimulates hypoxia inducible factor 1, the main regulator in the expression of the leptin gene-a hormone secreted by adipose tissue that has a negative feedback on appetite-and inversely associated with obesity (Sierra-Johnson et al 2008). A cross-sectional study conducted at different altitudes in the Everest region of Nepal also found that obesity decreased with increasing altitude (Sherpa et al 2010). Our findings present a striking example of the variation in obesity prevalence found among populations of similar indigenous backgrounds under different environmental circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new therapies are being sought to modify the cascade of injury–repair–regeneration of skeletal muscles. In many cases, regeneration-stimulating methods are implemented into clinical medicine to improve functional abilities in patients awaiting surgical interventions or suffering from chronic illnesses such as cardiovascular and rheumatic diseases [ 4 , 8 , 13 , 19 , 20 , 21 , 22 ]. NO and H 2 O 2 production is known to increase dramatically in injured skeletal muscle [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available studies reported substantial improvement in sea level endurance and anaerobic performance after IHE [ 4 , 5 , 6 ]. Beside the effects that hypoxia exerts on physical performance, there is some evidence that IHE might be beneficial for vascular endothelial activity and muscle regenerative capacity [ 7 , 8 ]. Hypoxic exposure increases production of reactive nitrogen and oxygen species (NO and H 2 O 2 ) and affects metabolic pathways including mitochondrial respiration and biogenesis, apoptosis and, what has more recently been demonstrated, satellite cells proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hypoxic exposure is one of the methods which have been used for decades by professional athletes to increase endurance, strength, and speed, to avoid fatigue and to improve recovery [ 5 7 ]. A few epidemiologic and physiologic observations have demonstrated positive effects of hypoxia conditions on cardiovascular health [ 8 10 ]. Being born at high altitude was shown to have an independent protective effect against coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regular physical activity with hypoxia exposure increases NO production via iNOS and eNOS [ 17 ], and thus, it could modify the lipid profile and inhibit the production of proinflammatory cytokines: tumour necrosis factor α (TNF α ) and interleukin 1 β (IL-1 β ) [ 18 21 ]. The majority of such observations were performed in healthy nonactive subjects or patients with coronary artery disease [ 10 , 22 25 ]. According to Angeli et al [ 25 ], the generation of inflammatory mediators in physically active men causes disturbances to vascular endothelial activity which precedes the development of arteriosclerosis.…”
Section: Introductionmentioning
confidence: 99%